2012
DOI: 10.1134/s0026261712020117
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of 4-chlorobiphenyl and 4-chlorobenzoic acid by the strain Rhodococcus ruber P25

Abstract: The strain Rhodococcus ruber P25 utilizes 4 chlorobiphenyl (4CB) and 4 chlorobenzoic acid (4CBA) as sole carbon and energy sources. 4CB degradation by washed cells of strain P25 was accompanied by transient formation of 4CBA, followed by its utilization and release of equimolar amounts of chloride ions into the medium. The strain R. ruber P25 possessed active enzyme systems providing 4CBA degradation via the stages of formation of intermediates, para hydroxybenzoate (PHBA) and protocatechuic acid (PCA), to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The presence of both orthoand metacleavage pathways in Sphe3 was also validated through proteomic analysis [29]. Although the occurrence of meta-cleavage of PCA has also been demonstrated in Arthrobacter keyseri 12B [30] as well as in other Actinobacteria [31], there is no study on the kinetic characterization of PCA 4,5-dioxygenase in this phylum. The functional and/or kinetic studies of enzymes belonging to the largely uncharacterized Type II extradiol dioxygenase clade of the PCAD-Memo superfamily will allow comparisons among these enzymes, thus shedding more light on this Type in the dioxygenase superfamily.…”
Section: Introductionmentioning
confidence: 97%
“…The presence of both orthoand metacleavage pathways in Sphe3 was also validated through proteomic analysis [29]. Although the occurrence of meta-cleavage of PCA has also been demonstrated in Arthrobacter keyseri 12B [30] as well as in other Actinobacteria [31], there is no study on the kinetic characterization of PCA 4,5-dioxygenase in this phylum. The functional and/or kinetic studies of enzymes belonging to the largely uncharacterized Type II extradiol dioxygenase clade of the PCAD-Memo superfamily will allow comparisons among these enzymes, thus shedding more light on this Type in the dioxygenase superfamily.…”
Section: Introductionmentioning
confidence: 97%
“…PCBs undergoes dehalogenation to lower chlorinated biphenyl and further to chlorobenzoic acid metabolite. These chlorobiphenyl is further converted into hydroxybenzoic acid and dihydroxybenzoic acid ( Zhai et al, 2010 ; Plotnikova et al, 2012 ). Bedard et al (1987) , have reported chlorinated benzoic acid and chlorinated acetophenone intermediate metabolites from oxidation of PCB congeners.…”
Section: Resultsmentioning
confidence: 99%
“…4‐CB1 (Crooks and Copley, ), Arthrobacter sp. (Zhuang et al ., ; Zhou et al ., ), Rhodococcus ruber P25 (Plotnikova et al ., ), Betaproteobacteria (Chae et al ., ). 4‐Chlorobenzoate can be used as a substrate for ATP‐dependent 4‐halobenzoate coenzyme A ligase in the cell to generate a reactive metabolite, 4‐chlorobenzoyl coenzyme A (Pieper, ).…”
Section: The Middle Metabolic Pathways For Dehalogenation Of Halogenamentioning
confidence: 99%